2009
DOI: 10.1099/vir.0.015446-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel circular DNA viruses in stool samples of wild-living chimpanzees

Abstract: Viral particles in stool samples from wild-living chimpanzees were analysed using random PCR amplification and sequencing. Sequences encoding proteins distantly related to the replicase protein of single-stranded circular DNA viruses were identified. Inverse PCR was used to amplify and sequence multiple small circular DNA viral genomes. The viral genomes were related in size and genome organization to vertebrate circoviruses and plant geminiviruses but with a different location for the stem-loop structure invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
72
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 59 publications
2
72
1
2
Order By: Relevance
“…Circovirus-like SF pork NW2 P7 genome is unusually small and only loosely related to circoviruses or cycloviruses and because of its unusual genome size and organization, its classification remains uncertain. The detection of apparently truncated circular DNA genome is reminiscent of that reported for a distantly related group of circular DNA viruses (ChiSCV) recently detected in chimpanzee stool (Blinkova et al, 2010) and could reflect the presence of defective genome requiring trans-complementation by a helper virus.…”
mentioning
confidence: 59%
“…Circovirus-like SF pork NW2 P7 genome is unusually small and only loosely related to circoviruses or cycloviruses and because of its unusual genome size and organization, its classification remains uncertain. The detection of apparently truncated circular DNA genome is reminiscent of that reported for a distantly related group of circular DNA viruses (ChiSCV) recently detected in chimpanzee stool (Blinkova et al, 2010) and could reflect the presence of defective genome requiring trans-complementation by a helper virus.…”
mentioning
confidence: 59%
“…Thus far, none of these viruses have been cultured or found in animal tissue sample. Nonetheless, the viruses have been discovered using viral metagenomics approaches and for the majority of the smacoviruses, the validity of genome sequences has been verified by either PCR amplification using abutting primers followed by Sanger sequencing of these products or by amplification, cloning and Sanger sequencing of the recombinant plasmids [1,3,4,9,15,22,24]. Camel associated porprismacovirus 1…”
mentioning
confidence: 99%
“…Metagenomics studies of animal feces have similarly shown frequent coinfections and yielded highly divergent viral species (10,16,25,30,43,44,50,52,53,57,60,61,64).…”
mentioning
confidence: 99%